Information support for decision making in problem situation description - S. F. Lipnitsky (Informatika)
Objectives. The problem of automating the user information support in decision making system at the stage of describing the problem situation is solved. The relevance of the problem is associated with the need to collect and process significant amounts of information, since in the presence of a large number of factors, a person's capabilities are often insufficient to search and organize the necessary information.When solving the problem of user information support at the stage of describing the problem situation, three main goals are pursued: building a mathematical model of the corresponding processes; formalization of the set of basic concepts of the model; development of the algorithms for implementation of user interaction with the information system.Methods. Methods of set theory, probability theory and graph theory are used.Results. A mathematical model of user information support at the stage of describing a problem situation has been developed. In the process of interacting with the user, the system suggests special templates of sentences and texts for filling. Along with templates, the user receives help texts from the system. They are generated on the basis of the previously developed model of knowledge representation in the form of verbal associations, that is, semantic links between words and phrases corresponding to associative relationships between the entities they designate in the real world.Conclusion. As an implementation of the proposed model, the following algorithms have been developed: an algorithm for creating a dictionary of communicative fragments; algorithms for creating fragment-slot templates for sentences, texts and subject areas; an algorithm of user information support. The vocabulary of communicative fragments is created in four steps in accordance with their formal definition. At each step, four conditions from the given definition are tested sequentially. Fragment-slot templates of sentences are formed by replacing their basic communicative fragments with slots, and text templates - as tuples of templates of their sentences. Fragment-slot templates of subject areas are created in the form of implementation of binary relations reductions on the sets of sentence templates from the corresponding thematic text corpora. Each thematic body of texts defines a certain subject area.